'My Lord Sue': Lady Susan Keck and the Great Oxfordshire Election of 1754. (1st October 2013) - Chalus, Elaine
Abstract : As one of the most memorable campaigners for the New Interest whigs in the Oxfordshire election of 1754, Lady Susan Keck inevitably became the subject of press ridicule and criticism. Undaunted and irrepressible, she not only continued to campaign, but also turned the criticism back on the Old Interest, effectively neutralising it. This detailed examination of Lady Susan's electioneering illustrates the possibilities for electoral involvement at mid‐century that were available to a woman of rank and spirit who was determined to make a difference. Propelled into action by sheer frustration with the poor planning and lacklustre campaigning that had marked the New Interest campaign in the 1751 election, Lady Susan put her, not inconsiderable, energy into securing a victory for the New Interest. Driven by ideology rather than by family interests, she used her age, rank, sex and connections, to political advantage. Confident and characterful, she was ideally suited to the rumbustious, personal politics of the age. Most importantly, her canvassing achieved results and the eventual New Interest victory owed, at least in part, to her efforts.